NOTCH activation promotes glycosyltransferase expression in human myeloid leukemia cells - Shichun Wang; Mai Itoh; Erika Shiratori; Mika Ohtaka; Shuji Tohda (Hematology Reports, 2018)
NOTCH signaling diversely regulates the growth of acute myeloid leukemia (AML) cells. It is known that glycosylation of NOTCH receptors modulates NOTCH activation. However, little is known about glycosylation of NOTCH in AML cells. We examined the effects of ligand-induced NOTCH activation on the expression of NOTCHmodifying glycosyltransferases in two AML cell lines, THP-1 and TMD7. The cells were stimulated with recombinant NOTCH ligands JAGGED1 and DELTA1, and subjected to immunoblot analysis to evaluate the expression levels of glycosyltransferases. Ligand stimulation promoted the expression of POFUT1, LFNG, MFNG, RFNG, GXYLT1, GXYLT2, and XXYLT1 in THP-1 cells, and that of RFNG and GXYLT1 in TMD7 cells. We found that NOTCH activation promoted the expression of several glycosyltransferases in AML cells. This suggests that NOTCH activation modulates its sensitivity to NOTCH ligands by increased glycosylation of NOTCH receptors in AML cells. Further investigation is needed to elucidate its biological significance.